Charting Our Course: Chaplain Documentation as a Performance Improvement Project. Issue 4 (2nd October 2018) - Tartaglia, Alexander; Ford, Timothy; Dodd-McCue, Diane; Reid, Christine; Hawley, Carolyn; Hassell, Alma
Abstract : This article presents the results of a 30-month process improvement initiative examining the spiritual assessment documentation patterns of staff chaplains as well as CPE residents and interns at an academic medical center. Preliminary examination of chaplain documentation patterns led to a multidimensional intervention to address perceived documentation limitations and enhance reliability. The intervention resulted in positive changes in documentation patterns as assessed by an expert panel of experienced chaplains. Results offer opportunities for the use of electronic medical record documentation in training of chaplains.